Next-generation sequencing identifies CDKN2A alterations as prognostic biomarkers in recurrent or metastatic head and neck squamous cell carcinoma predominantly receiving immune checkpoint inhibitors - Xue, Liqiong; Tang, Wenbo; Zhou, Jiuli; Xue, Junli; Li, Qun; Ge, Xiaoxiao; Lin, Fengjuan; Zhao, Wei; Guo, Ye (Frontiers in Oncology, 2023)
Background: This study aimed to identify potential biomarkers in patients with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC) and further probe the prognostic implications of CDKN2A mutations, particularly within a subset receiving immunotherapy. Methods: In this retrospective single-center study, we evaluated the next-generation sequencing (NGS) data from Foundation Medicine (FM) for patients with recurrent or metastatic HNSCC between January 1, 2019, and December 31, 2021. Patients were stratified based on CDKN2A loss-of-function (LOF) versus wild-type (WT) categorizations, with a focused subgroup analysis on those administered immunotherapy. Results: The study encompassed 77 patients, of which 62 had undergone immunotherapy. The median duration of follow-up was 22.6 months. For the CDKN2A LOF group, the median overall survival (OS) was 16.5 months, contrasted with 30.0 months in the CDKN2A WT group (P=0.014). Notably, female gender (hazard ratio [HR]=4.526, 95% confidence interval [CI]: 1.934-10.180, P=0.0003) and CDKN2A LOF (HR=2.311, 95% CI: 1.156-4.748, P=0.019) emerged as independent risk factors for mortality in patients with recurrent or metastatic HNSCC. Within the immunotherapy subset, the median OS was 11.7 months for the CDKN2A LOF group, and 22.5 months for the CDKN2A WT group (P=0.017). Further, the female gender (HR=4.022, 95% CI: 1.417-10.710, P=0.006), CDKN2A LOF (HR=4.389, 95% CI: 1.782-11.460, P=0.002), and a combined positive score below 1 (HR=17.20, 95% CI: 4.134-79.550, P<0.0001) were identified as significant predictors of mortality among patients with recurrent or metastatic HNSCC receiving immunotherapy. Conclusion: Alterations manifesting as LOF in the CDKN2A gene stand as robust indicators of unfavorable survival outcomes in HNSCC patients, including the subset that underwent immunotherapy.